EFFECTS OF TADALAFIL AND/OR SILYMARIN ON GONADAL FUNCTION IN ADULTS MALE ALBINO RATS (Basrah Journal of Veterinary Research)
Taldalafil is a long acting phosphodiesterase-5 inhibitor  widely used in the treatment of erectile dysfunction. The abuse of tadalafil, which is a worldwide problem, is associated with many side effects. Sylimarin considered as a herbal drug, its active constituents  are silybin, isosilybin, silydianin and silychristin. A controversy exist with regard to the effects of tadalafil and silymarin on gonadal function in animal species. The present study aimed to investigate the effects of tadalafil and/or sylimarin on gonadal function adult male rates. Twenty four male rats are  used in the study, they divided into 4 groups (n=6) and gavaged daily for 1 month as follows; 1-control(0.5ml distilled water), 2-tadalafil (10mg tadalafil/kg ), 3-silymarin (100 mg silymarin/ kg) and 4-tadalafil + silymarin ( 10 mg tadalafil and 100 silymarin mg/ kg). Tadalafil significantly increases serum testosterone and decreases LH and FSH, it adversely affect the process of spermatogenesis (sperm count and percentage of motile, dead, and abnormal sperms). While, silymarin significantly increases serum testosterone, LH and FSH and improve spermatogenesis. Serum testosterone remains significantly higher in tadalafil+silymarin group compared with control group, while FSH and LH and parameters of spermatogenesis became insignificantly different from those in control group.